Penentuan Jumlah Pengambilan Barang Guna Meningkatkan Service Level pada PT. XY - Wati, Putu Eka Dewi Karynia; Amalludin, Luqman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study examines inventory control for two major cement products, Semen Gresik and Semen Merdeka, at PT XY Sidoarjo Branch, aiming to minimize stockout risk and financial losses arising from lost sales and delivery penalties. Operational data from June to August 2025 were analyzed to identify demand patterns, supply fluctuations, and the need for accurate determination of safety stock and reorder point. The findings indicate several stockout events that contributed to significant financial losses, amounting to approximately Rp509,600,000 for Semen Gresik. Therefore, a more precise inventory control approach is required, particularly through the Continuous Review method, which considers daily demand variability and lead time. The proposed improvements include implementing a more adaptive safety stock level and adjusting the reorder point to reduce stockout frequency and enhance distribution reliability.